Die Relativität des Raumes und der Zeit. Stürzte Einstein das Newtonsche Weltbild? - Wahsner, Renate (Revista de Filosofía, 2005)
The widespread perception, according to which Einstein brought down the Newtonian worldview, is based on the inadmissible identification of physical theory Mechanics founded by Newton with the philosophical interpretation of this science by the mechanistic worldview. However, Newtonian mechanics is the basis of modern physics. The evolution from Newtonian to Einsteinian space-time theory reduced the quasi-apriori part of physics and exhibited the function of physical space. As a result of this, Kantian space apriorism appeares in a new light